Prevalence De L’insuffisance Cardiaque Au Cours De La Grossesse Et Dans Les Suites De Couches En Milieu Hospitalier A Parakou En 2015 - Houétondji, Codjo Léopold; Mahougnon, Adjagba Philippe; Arnaud, Sonou Jijoho; Murielle, Hounkponou; Fanny, Hounkponou; Mahougnon, Dohou Serge Hugues; Ingrid, Djoh Khadidja; Adébayo, Alassani; Séraphin, Ahoui; Martin, Houénassi Dèdonougbo (European Scientific Journal, ESJ, 2018)
Introduction: Heart failure is one of peripartum complications which contribute to maternal mortality. But the epidemiological features of this disease are not well known in Benin. This paper aims at studying the prevalence and associated factors of heart failure during pregnancy and the postpartum in Parakou in 2015. Methods: It was a descriptive and analytic cross sectional study scheduled from March to July 2015. We recruited systematically all pregnant or parturient women, met in Parakou’s hospitals. The inclusion criteria were the presence of at least one cardiovascular symptom. Diagnosis of heart failure was made by using the guidelines of the European Society of Cardiology and of the American Society of Echocardiography. Results: During the survey, 2503 pregnant or parturient women were admitted and 25 (0,99%) were diagnosed with heart failure. Dyspnea was the main symptom (96%). Heart failure was caused by peripartum cardiomyopathy(84%), hypertensive cardiomyopathy (12%) and rheumatic heart disease (4%). Heart failure was more prevalent in patients with the following conditions: age≥30years (p=0,001), low socioeconomic level (p=0,02), multigestational status (p=0,002) and multiparity (p<0,001). The management of heart failure was classic. The main difficulty noted was financial problems with 36% of patients unable to afford the treatment. No case of death was counted during the study. Conclusion: In Parakou, heart failure occurs mostly during the post partum period. Dyspnea was the main symptom. The main etiology was peripartum cardiomyopathy. The associated conditions were age≥30years, low socioeconomic level, multigestational status and multiparity.